Clinical and Functional Outcomes of Percutaneous Locking Plate as an External Fixator in Extra-Articular Proximal Tibia Fractures: Locking Plate as External Fixator in Proximal Tibia Fractures - Imran Manzoor; Rizwan Khan Lodhi; Muhammad Moeen; Jahanzeb Khan; Imanullah Riaz; Muhammad Omer Imran Elahi (Journal of University College of Medicine and Dentistry, 2025)
Objective: To evaluate the clinical and functional outcomes of using a percutaneous locking plate as an external fixator in extra-articular proximal tibia fractures, with particular emphasis on pain reduction, fracture union, and progressive recovery of knee range of motion (ROM). Methodology: This prospective interventional study was conducted in the Department of Orthopedic Surgery at Hayat Memorial Hospital, affiliated with Continental Medical College, Lahore, over a 12-week period from January to March, 2025. A total of 30 patients, aged 18 to 75 years, with open extra-articular proximal tibia fractures were included using consecutive non-probability sampling. Fracture stabilization was performed using a 12- or 19-hole locking compression plate applied externally. Pain was assessed at 1, 3, 6, and 12 weeks postoperatively using the Wong-Baker Faces Pain Rating Scale, while ROM was measured using a goniometer. Radiographic evaluation for union was conducted at the same intervals. Data were analyzed using SPSS version 23, with p < 0.05 considered statistically significant. Results: The study included 30 patients (mean age 43.5 ± 12.2 years; 21 males and 9 females). Average pain scores showed a statistically significant decline from 6.0 in the 1st week to 1.5 by the 12th week (p < 0.05). ROM also improved progressively: at the 1st week, most patients were limited to 30°–60°, whereas by the 12th week, the majority (n=23) achieved near-normal ROM (120°–135°). Radiographic union was observed in all patients by the end of 12 weeks. Conclusion: Percutaneous application of a locking compression plate as an external fixator appears to be an effective treatment option for extra-articular proximal tibia fractures. It offers stable fixation, reduces pain significantly, and facilitates early functional recovery in terms of knee mobility.